THE INFLUENCE OF USING SHORT STORY TOWARDS STUDENTS’ ABILITY IN COMPREHENDING NARRATIVE TEXT AT THE SECOND SEMESTER OF THE EIGHTH CLASS AT SMP NEGERI 2 SUMBER REJO TANGGAMUS - Alfiawati, Riska (LPPM STKIP PGRI Bandar Lampung, 2018)
Comprehension is the purpose of reading. Without it the reader wastes her time because she is not processing and remembering the text. It is vital to the education of students to implement strategies to develop reading comprehension skills. The students with literacy problems who do not receive help are in danger of becoming adults with limited employment opportunities and other life challenges. The purpose for reading and the type of text determine the specific knowledge, skills, and strategies that readers need to apply to achieve comprehension. Reading comprehension is thus much more than decoding. Reading comprehension result is when the reader knows which skills and strategies are appropriate for the type of text, and understand how to apply them to accomplish the reading purpose. The objective of this research is to know and describe the influence of using Short Story towards students’ ability in comprehending narrative text. This research was conducted by using Experimental method. The total population of this research was 150 students in 5 classes. The samples of this research were 2 classes. In taking the sample, the writer used cluster random sampling technique. In getting the data, the writer used multiple choices test with 40 item test. Based on data analysis and hypothesis, the writer found that the average score of students’ ability in comprehending narrative text who are taught by using Short Story was higher than that of those who are taught through conventional technique (= 71.58 >= 57.42). Therefore the calculation of ttest = 7.01 was higher than ttable with significance 5% = 1.67 and significance 1% =2.39. The writer then concludes that there is a significant influence of Short Story towards students’ ability in comprehending narrative text for the students at the second semester of the eighth class at SMP Negeri I Sumber Rejo Tanggamus in 2012/2013.